Factors affecting general practitioners' decisions about plain radiography for back pain: implications for classification of guideline barriers - a qualitative study - Baerheim Anders; Espeland Ansgar (BMC, 2003)
Abstract Background General practitioners often diverge from clinical guidelines regarding spine radiography. This study aimed to identify and describe A) factors general practitioners consider may affect their decisions about ordering plain radiography for back pain and B) barriers to guideline adherence suggested by such factors. Methods Focus group interviews regarding factors affecting ordering decisions were carried out on a diverse sample of Norwegian general practitioners and were analysed qualitatively. Results of this study and two qualitative studies from the Netherlands and USA on use of spine radiography were interpreted for barriers to guideline adherence. These were compared with an existing barrier classification system described by Dr Cabana's group. Results The factors which Norwegian general practitioners considered might affect their decisions about ordering plain radiography for back pain concerned the following broader issues: clinical ordering criteria, patients' wishes for radiography and the general practitioner's response, uncertainty, professional dignity, access to radiology services, perception of whether the patient really was ill, sense of pressure from other health care providers/social security, and expectations about the consequences of ordering radiography. The three studies suggested several attitude-related and external barriers as classified in a previously reported system described by Dr Cabana in another study. Identified barriers not listed in this system were: lack of expectancy that guideline adherence will lead to desired health care process, emotional difficulty with adherence, improper access to actual/alternative health care services, and pressure from health care providers/organisations. Conclusions Our findings may help implement spine radiography guidelines. They also indicate that Cabana et al.'s barrier classification system needs extending. A revised system is proposed.